Study of histopathological and Histochemical changes Caused by Toxoplasma gondii in Vision Systems of Mice congenitally infected and the synergistic effect of Malarone and Clindamycin (NTU Journal of Agriculture and Veterinary Science, 2021)
The present work was conducted aiming at isolating and diagnosing Toxoplasma gondii from the placentae of infected women and inducing infection in female Swiss albino mice, through intraperitoneal injection resulted in 100% infection rate. Evaluation of malarone and clindamycin, single and synergistic between them in infection of female mice on the tenth day of gestation and delivery and confirmation of congenital infection, treatment was started at the age of one month with the above mentioned drugs. The criteria considered were the number of dead mice, the percentage of survival, and the average number of brain tissue cysts. Treatment with the synergized malarone and clindamycin were used to treat congenitally infected mice, number of death was not reported and the survival rate was 100%. Average numbers of brain tissue cysts are reduced to 5.55 in adult infected mice and the cure rate was 100%.Histopathological effects that occurred in the congenitally affected females, they were the appearance of hyperplasia and introversion of the retina several folds and the presence of scars that connect the retina to the choroid, and the reduction of the visual papilla, and it was noted for the first time by using the Congo red stain, signs of amyloid deposits in the vitreous fluid and in the debris of the lens that appeared irregular and seemed filled with fluid. And fatty materials and debris residues of lentil fibers. It was observed for the first time that the optic nerve was doubled using Mallory's triple stain. As for the brains, the same changes were observed, and amyloidosis appeared using the toludine stain. When using the treatment malaron and clindamycin at a dose of 100 mg/kg synergistically, the effect of infection in the eyes was slight and a noticeable improvement appeared in the brains.As for the histochemistry of stains and their components, and brain, different response were noted between strong +ev control and –ev for those treated with the two drugs malarone and clindamycin at a dose of 200mg/kg with PAS stain and Alician blue stain pH 2.5%. For Von kossa stain and Pearl`s stain, different responses also appeared in the eyes and the brains.For Feulgen stain, used to detect apoptosis good results was obtained in eyes, brains .